Factors Influencing Visits by Baduta Children in the Discovery of Pneumonia at the Way Halim II Health Center - Agung Prasetiyo; Achmad Djamil; Noviani Noviani (Journal of Education Technology Information Social Sciences and Health, 2024)
The discovery of pneumonia in toddlers is one of the efforts made to control pneumonia. The very low pneumonia coverage indicates that there are many cases where parents do not take them for treatment to the health center or take them to private health facilities. The aim of the research is to determine the relationship between knowledge, attitudes, distance, family support and the role of cadres with baduta visits in the discovery of pneumonia at the UPT Puskesmas Way Halim in 2023. Type of quantitative research, with a cross sectional approach design. The population in this study were all mothers who had children in the working area of the Way Halim II Health Center UPT, a total of 407 mothers and a sample of 80 respondents who were women and children. Based on the results of the research that has been carried out, researchers concluded that the majority of mothers, namely 52 mothers (65%) did not visit and carry out examinations at the Community Health Center, 48 mothers (60%) had poor knowledge, there were 42 poor mothers (52.5%) have a poor attitude, as many as 55 respondents (68.8%) fall into the category of moderate distance from home from the health center, as many as 53 mothers (66.3%) have poor family support, there are 46 respondents (57.5%) who say that the role of cadres is good. Based on the research results, there is a relationship between mother's knowledge (p-value 0.022), attitude (0.002), distance (0.002), family support (0.024) and there is no relationship between the role of cadres (0.319) and the child's visit to the health center. Way Halim II Bandar Lampung. The suggestion is that mothers are expected to be more responsive and always make visits and examinations to community health centers in an effort to find pneumonia in the working area of Way Halim II Bandar Lampung Public Health Center UPT.